Recognition and legal protection of polygamic relationships consolidated abroad (Research, Society and Development, 2022)
Knowing that one of the outstanding characteristics of globalization is the intensification of flows of people with different cultures between countries, the problems faced by these immigrants are addressed with regard to the diversity of cultural values ​​and how to guarantee and protect their rights. Assuming that Brazil receives immigrants whose culture and beliefs allow for consenting polygamy in their relationships, the objective of this work to assess whether there is a construction of space where the minimum right is preserved, so that a peaceful and balanced coexistence, how plural families are treated and what are the values ​​and arguments used so that there is the possibility of recognizing these families. As for the research, the approach is bibliographical, qualitative and exploratory and aims to analyze, among many laws, whether the Migration Law nº 13.445 of May 24, 2017, which reinforces respect for human rights and guarantees, provides guidance for dealing with these differences, and whether Brazil recognizes and welcomes these family arrangements. This work concludes with the perception that there is much to be done, giving a more human approach to the essence of the citizen and his culture, so that the fundamental and natural rights that are inherent to any human being are not omitted.